THE DEVELOPMENT OF THE FIRST DEPARTMENT OF MANAGEMENT IN OUR COUNTRY - G. R. Latfullin (Вестник университета)
The formation, development of the theory and methodology of management science have been revealed on the example of the First Department of Management in our country. Meanwhile, the role of the Department in the organization of 15 theoretical, branch, functional management departments at the University has been highlighted. The activity of the Department marked the beginning of management in the Institute, it served as a source of distribution in it managerial “spirit”, the ideology of manageability. The article designates new concepts and modern methodologies for the development of management science at the present stage: innovative digital economy and management, anthropologization, value and project approaches. Modern approaches to management education, creation of universities of new formation, with allocation of their main functions have been considered. The role of the teaching staff of the Department in the development of management science has been rightly emphasized, the special role in this work belongs to Kozlova Olympiada Vasilievna.